ANALISIS KASUS TENTANG POLIGAMI YANG DILAKUKAN OLEH PEGAWAI NEGERI SIPIL (PNS) TANPA IZIN ISTRI PERTAMA (STUDI PUTUSAN MAHKAMAH SYAR’IYAH BANDA ACEH NOMOR: 130/PDT-G/2013/MS-BNA) - JURAIDA JURAIDA (PREMISE LAW JURNAL, 2016)
Marriage registration is a state’s administration which is done by state official (Registrar for Marriages) in a marriage. Marriage registration in the Religious Affairs Office is needed for a person to have a legal document as authentic evidence before the Court. A registered marriage is intended to get legal certainty and order and to protect the status and sanctity of a marriage, particularly to protect women and children in wedlock when there is a dispute in a married life. Marriage registration by Registrar for Marriages is regulated in Law No. 1/1974 on Marriage, the Government Regulation No. 9/1975 on the Implementation of Law No. 1/1974 on Marriage, and KHI (Compilation of the Islamic Laws). Registrars for the Marriages as government officials appointed by the Minister of Religious Affairs in each subdistrict in their duties to examine the requirements, supervision, and marriage registration, have not done their duties correctly: they receive inadequate administrative requirements and have not control marriage contracts. In the procedure of the issuance of marriage books outside of the place where a marriage occurs, a Registrar for Marriages outside of the place where a marriage occurs should make request to the Registrar for Marriages where the marriage occurs so that a marriage book can be issued. Administrative sanction will be imposed on any Registrar for Marriages who violate this regulation. Keywords: Polygamy, Government Employees, Without Permission from the   First Wife